International survey of awareness of genetic risk in the clinical sarcoma community. Issue 2 (29th February 2016) - McBride, Kate A; Schlub, Timothy E; Ballinger, Mandy L; Thomas, David M; Tattersall, Martin HN
Abstract: Aim: Integration of clinical genetics into oncology is variable. Sarcomas have a strong genetic component, with up to 1/30 patients carrying germline TP53 mutations. This study aimed to define genetic risk awareness among sarcoma physicians. Outcomes were attitudes toward genetic testing, level of cancer risk and awareness of risk reduction measures. Methods: An online survey was administered to members of the Connective Tissue Oncology Society and the Australasian Sarcoma Study Group. Results: Sarcoma physicians ( N = 124) from 21 countries participated, 40% of whom favored TP53 mutation testing in children regardless of family history, increasing to ∼83% for all age groups if a family history was present and ∼85% if multiple primary cancers were present. However, 33% were not aware that risk reduction strategies might identify some cancers at a more curable stage in carriers. Conclusion: Clinical genetics is not yet standard of care for multidisciplinary management of sarcoma. Awareness of genetic risk is important among sarcoma physicians. Attitudes among the sarcoma community were generally positive, but education on genetic risk in sarcoma patients and collaboration with clinical genetics services might improve quality of care. Sarcoma physicians need routine access to clinical genetics services so that potential germline TP53 mutation carriers are recognized.